PKM beras ketan hitam desa kalimas kecamatan sungai kakap kabupaten kubu raya - Susana Susana; Evi Sofiana (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
The PKM partner is a farmer group in Kalimas Village, Kakap District, Kubu Raya Regency, West Kalimantan. The problems faced by partners are: 1) human resources who have knowledge and skills about processing technology for agricultural products, 2) partners have an entrepreneurial spirit, 3) expertise on appropriate technology that can be applied to entrepreneurship, and 4) Partners do not have the knowledge and applied skills in the field of business marketing. Solutions for community partnership programs include: 1) enhancing human resource knowledge and skills, 2) building entrepreneurial enthusiasm, 3) providing knowledge in theory and practice encompassing the overall expertise of appropriate technology that can be applied to entrepreneurship, and 4) provide knowledge and skills in product processing and product marketing. Output Targets; 1) knowledge and skills of human resources increase, 2) foster an entrepreneurial spirit, 3) partners have the knowledge and skills in implementing appropriate technology, 4) partners have the knowledge to manage a business management system, and 5) partners have the product marketing knowledge and skills and can implement them. The method to be applied in achieving the objectives of the activity is; 1) socialization, training and processing assistance, 2) business management training, 3) training and product marketing demonstration, 4) assistance in product marketing the results of PKM activities are partners having skills in processing black sticky rice into products that have added value and partners having motivation to develop business of processed black sticky rice